From Mosques to Cafes: Muslim Youth and Mawlid Celebration in Yogyakarta - Wahyudi, Muhammad (Universitas Islam Internasional Indonesia, 2023)
Abstract The celebration of Mawlid has sparked ongoing discussions among traditionalist and modernist Muslims. Traditionalists perceive Mawlid as a cherished tradition symbolizing joy and love for Prophet Muhammad, passed down through generations. Conversely, modernists often deem it heretical, indicating a societal decline. Within this discourse, an unconventional Mawlid phenomenon has emerged—celebrations hosted in cafes in Yogyakarta, primarily attended by Muslim youth, in contrast to the traditional mosque gatherings of older generations. The Cafe-based Mawlid celebration is characterized by a relaxed atmosphere, humor, simplified lectures, and diverse participation, stand out for their uniqueness. This qualitative, phenomenological study delves into the dynamics of Mawlid celebrations in Yogyakarta's cafes, seeking to unveil the motivations propelling Muslim youth participation. This paper argues that the evolution of Mawlid celebrations, initially confined to mosques and exclusive to traditionalist Muslim groups, has now transitioned to public spaces like cafes, welcoming diverse participants. his shift underscores the dynamic interplay between religious traditions and the changing socio-cultural landscape. Keywords: Mawlid, Muslim Youth, Social Action, Husein Ja’far